(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
Through the Victorian age in England, woman suffered a lot and treated as a commodity that was sold to the one who would pay more. It was vital for the rich families to maintain their high esteemed social rank through choosing the right husbands for their daughters. The latters feelings were not adequately reckoned since they did not have the upright sensible thinking to choose for themselves. The hierarchical order was to be imposed and respected regardless the daughters’ prospects. This aroused some concern and sympathy in some literary writers in the Victorian England. Of them was Lord Alfred Tennyson who sustained the woman’s cause and exposed her plights. He called for freeing her from the yoke of the rude male’s domination so as to enhance her part in society.